Peran Media Sosial Dalam Mempengaruhi Identitas Sosial Remaja Di Era Digital - Irma Tiur Christ Zai; Alva Nathaniel Zebua (CV. SINAR HOWUHOWU, 2024)
The development of digital technology, particularly social media, has brought significant changes in adolescents' social interactions and self-identity formation. This journal discusses the role of social media in shaping adolescents' social identities in the digital age, highlighting both the benefits and risks associated. Social media provides a platform for adolescents to express themselves, build social relationships, and explore various identities. However, excessive use of social media can lead to negative impacts, such as anxiety, depression, and the influence of unrealistic beauty standards. In addition, the risk of cybercrime and the spread of inappropriate content is also a concern. Therefore, it is important to improve media literacy among teenagers and provide proper guidance from parents and educators. With a wise approach, social media can be utilized as a tool that supports the development of a healthy and positive social identity for young people. This research is expected to provide insights for parents, educators, and policy makers in understanding and managing the use of social media among adolescents.